ANALISIS BLACKSPOT DI INDONESIA BERDASARKAN PERBEDAAN KONDISI JALAN, FATALITAS KECELAKAAN, DAN ANALISIS RISIKO - Sutandi, Anastasia Caroline (Jurnal Jalan Jembatan, 2023)
Blackspot is a prone location with a high number of accidents. There are a number of definitions of blackspot, i.e. based on country, location, and the severity of road traffic accidents (accidents). One definition of blackspot in Indonesia is a location of 300 up to 500 meters long with a high number of accidents. Usually, blackspot is only analyzed based on the number of accidents and the severity of accidents. In this study, blackspot is analyzed based on 3 criteria i.e. (1) differences in road conditions, (2) the number of accident fatality, and (3) risk analysis in a specific time period. The differences in road conditions in terms of geometric conditions, road pavement surface conditions, and road furniture conditions. The number of accident fatality data can be taken from the National Police of the Republic of Indonesia or from the Central Bureau of Statistics in Indonesia. Risk analysis is an analysis to determine the risk value, risk category, and action recommendation in order to reduce the number of accidents and the fatality of the accident. Furthermore, comparison is carried out between determination of blackspot location based on the number and the severity of accident and those based on the three criteria. The results based on the three criteria show that determination of blackspot location is more accurate. The results of the study produce a more accurate and detailed blackspot analysis and can be used in all locations in Indonesia using complete, accurate, and up-to-date accident data, so that the results are valid and useful for explaining actual real conditions.